2019
DOI: 10.5812/modernc.96468
|View full text |Cite
|
Sign up to set email alerts
|

Protective Role of Training and Selenium Consumption Against Renal Toxicity Induced by Cadmium in Rats

Abstract: Background: Cadmium is a toxic metal, which can cause damage to the renal tissue. Various studies have suggested the protective role of training and selenium as a cofactor involved in the production of antioxidants in acute and chronic kidney disease, although the molecular-cellular mechanism of these two interventions is still not fully understood in the renal tissue. Objectives: The aim of this study was to investigate the protective effects of training and selenium consumption on the renal tissue of cadmium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“…Recent studies have shown that Cd can accumulate in the kidneys and lead to nephropathy (Madden and Fowler 2000;Kayaaltı et al 2015). Our results were similar to previous studies (Kido et al 1990;Renugadevi and Prabu 2009;Aranami et al 2010;Renugadevi and Milton Prabu 2010;Momeni et al 2019;Goodarzi et al 2020) and clearly showed that acute Cd exposure increases serum levels of urea, creatinine, ALP, TBIL and uric acid (Figure 2). Cd ions cause severe glomerular and tubular damage and mainly affect the proximal tubules, the site of maximum absorption.…”
Section: Discussionsupporting
confidence: 92%
“…Recent studies have shown that Cd can accumulate in the kidneys and lead to nephropathy (Madden and Fowler 2000;Kayaaltı et al 2015). Our results were similar to previous studies (Kido et al 1990;Renugadevi and Prabu 2009;Aranami et al 2010;Renugadevi and Milton Prabu 2010;Momeni et al 2019;Goodarzi et al 2020) and clearly showed that acute Cd exposure increases serum levels of urea, creatinine, ALP, TBIL and uric acid (Figure 2). Cd ions cause severe glomerular and tubular damage and mainly affect the proximal tubules, the site of maximum absorption.…”
Section: Discussionsupporting
confidence: 92%